Peran Regulasi Terhadap Anggota TNI Pelaku Tindak Pidana Desersi Dalam Perspektif Hukum Militer - Azzahra, Novita Fitria; Triadi, Irwan (Media Hukum Indonesia (MHI), 2025)
The criminal act of desertion is a serious offense that can significantly impact and undermine the discipline and operational readiness of the military institution if committed by members of the Indonesian National Armed Forces (TNI). This article examines the factors contributing to desertion and the role of regulations in addressing this issue under military law. The study employs a normative juridical method by analyzing various regulatory sources, such as the Military Criminal Code (KUHPM) and the internal policies of the TNI. The findings indicate that psychological pressure, along with internal and external stressors, are key triggers of desertion. Although law enforcement against desertion cases under military law has been implemented, strategic measures are still needed to enhance the welfare of military personnel and strengthen the overall system to prevent such offenses.